Inspiring Confidence and Professional Growth in Leadership: Student Perspectives on University-District Partnership Master's Academies - Pilar Mejía; Samrie Devin; Heather Calvert (Educational Considerations, 2016)
School leadership matters when discussing teacher effectiveness and student performance, and preparation programs need to graduate principals with the skills necessary to lead schools for tomorrow. The traditional approach to preparing educational leaders is no longer getting the job done. It is going to take everyone working together to better prepare those who will lead the schools we need.
Keywords: Partnership; Inspiring; Perspectives; Kansas State; Academy; Benefits; Model; data; leadership; responsibilities; performance; classroom